Teaching Legal English with “Modified Clil” - Dundon John Terry (Sciendo, 2021)
This paper will describe the methodology for teaching legal English used at the Fordham University School of Law’s Legal English Institute (LEI), a one-semester program for law students and attorneys. Reasonable minds may disagree about the most effective methodology for teaching legal English, or for that matter any other form of academic English, but we have developed an approach that is informed by both theory and practice. At LEI, we use a “modified CLIL” format, with four substantive classes on topics in U.S. law that run in parallel with a core class on legal English. All four substantive classes use authentic reading materials that are similar to those used in an LL.M. program, and these materials are recycled in the legal English class and form the basis of discussions about language issues. Our use of content classes (as opposed to explicit language classes) to elicit language issues has proven to be effective and it also helps keep students motivated, as students tend to have more intrinsic interest in legal topics than in language study per se.